(untitled) (Medical Forum Monthly, 2024)
Background: Despite advances in the prevention and treatment of hypertension over the past decade, hypertension remains an important public health challenge. Recent efforts to reduce the prevalence of hypertension have been focused on non-pharmacologic means, specifically diet. An increased in take of magnesium has been shown in some but not all studies to reduce blood pressure in patients with hypertension. Decreased Serum magnesium levels are associated with development of hypertension. Aim: This study was planned to investigate relation of serum magnesium with blood pressure in patients with mild uncomplicated hypertension. Place and Duration of Study: Study was conducted at LUMHS hospital Jamshoro and DHQ hospital charssadda for the period of six months. Patients & Methods: Fifty known cases of uncomplicated mild hypertensive patients were selected, same number of healthy controls were also examined. Results: When results were summed up and test parameters were compared, it was seen that no significant differences were found in serum magnesium levels among both groups, when compared statistically. Conclusion: Finally we conclude that no relation of magnesium with hypertension was observed. Suggestions: Much more work on wide scale population may be needed to clarify the idea.